Analysis of Religious Values in the Movie Ayat-Ayat Cinta 2 from the Perspective of Islamic Religious Education - Yazid Abdul Aziz; Abu Yazid Adnan Quthny; Nuramin Nuramin (Institut Nalanda, 2026)
This study aims to analyze the religious values portrayed in the movie Ayat-Ayat Cinta 2 from the perspective of Islamic Religious Education (PAI). The research employed a qualitative approach using a library research design and content analysis techniques. The primary data source was the film Ayat-Ayat Cinta 2, while secondary data were obtained from books, journals, articles, and other relevant scholarly literature. Data were collected through documentary observation and literature review, while data validity was strengthened through theoretical triangulation and in-depth interviews with experts in Islamic education and media studies. The findings indicate that the film represents three major dimensions of religious values, namely aqidah (Islamic creed), sharia (Islamic law), and akhlaq (Islamic morality). The main character, Fahri, is portrayed as an ideal Muslim figure who demonstrates strong faith, consistency in worship, tolerance, patience, and social concern for others regardless of religious differences. Furthermore, the film reflects the principles of religious moderation (wasathiyah) and the concept of Islam as Rahmatan lil ‘Alamin (a mercy to all creation). This study also finds that Ayat-Ayat Cinta 2 is relevant as an alternative instructional medium for Islamic Religious Education at the senior high school level because it can stimulate students’ emotional engagement and strengthen character education through audio-visual learning. Therefore, the film can serve as an innovative and contextual educational medium in Islamic learning and teaching practices.